Enhanced photocatalytic H2 evolution based on a polymer/TiO2 film heterojunction. (December 2022) - Wei, G.; Niu, F.; Wang, Z.; Liu, X.; Feng, S.; Hu, K.; Gong, X.; Hua, J.
Abstract: Polymer heterojunctions have emerged as promising photocatalysts for the photocatalytic hydrogen evolution. However, they are usually used in the form of suspended powder due to the low solubility and lack of anchoring groups to hybridize with inorganic semiconductor oxides. Yet polymer film heterojunctions with convenient separation and recycling potential are more suitable for large-scale water splitting. Herein, a new solution-processable polymer PDBCOOH with biphenyl as the electron donor and diketopyrrolopyrrole (DPP) containing carboxyl group as the electron acceptor has been designed and synthesized. Surface anchoring of PDBCOOH to TiO2 films through covalent bonding formed polymer-TiO2 film heterojunctions that achieved a recorded photocatalytic H2 production rate of 11.9 mmol/m 2 /h without Pt co-catalyst and was 88.8 times higher than that of pristine TiO2 film. Transient absorption spectroscopy confirms ultrafast polymer excited state electron injection into TiO2, long-lived charge separated state, and unity yield of polymer hole regeneration. Photoelectrochemical experiments combined with density functional theory calculation further demonstrate that polymer PDBCOOH /TiO2 film heterojunctions not only accelerate the charge transfer but also significantly improve the hydrogen evolution rate and stability of the photocatalysts. This work offers a new strategy for obtaining stable and efficient photocatalysts by using the covalent anchoring strategy of polymer/TiO2 film heterojunction. Highlights: Polymer/TiO2 film heterojunction for photocatalytic H2 evolution was constructed. The polymer/TiO2 film heterojunction can accelerate the charge separation. The recorded photocatalytic H2 production rate of 11.9 mmol/m 2 /h was achieved. The polymer/TiO2 film heterojunction improve stability of the photocatalysts.